A residência multiprofissional em saúde da família: revelando sentidos dos profissionais egressos - Campelo, Guassiane de Oliveira (2015)
The Federal Constitution ensures SUS (Unified Health System) as the regulator in the education of health professionals, which gave rise to ever-increasing attention to training in the area, for it must be in accordance with the principles established by the system. So, the Ministry of Health, in a partnership with the Ministry of Education, has invested in many programs aiming at the redirection of education, where Multidisciplinary Residency poses as a major improvement. Among these, Multidisciplinary Residency in the Family Health Program is challenged to prepare professionals to act in Basic Health Care. Thus, this research seeks to analyze practices of professionals coming from the Multidisciplinary Residency in Family and Community Health Program of the State University of Piauí (RMSFC/UESPI), presenting the following specific objectives: to know their academic and professional background; to investigate the practical use of the concepts learnt during Residency; to identify the aim of actions developed by these professionals in the workplace, as well as their contributions for redirecting health care practices. For such, this study adopted an exploratory-descriptive qualitative methodology, which is based on the methodological references of the “discursive practices and the production of meaning”, designed by Spink and collaborators. The study interviewed fifteen professionals egressed from the first groups of RMSFC/UESPI. The participants, all of which were females, aged on average 29.9 years old and had finished college on average 6.3 years before. The data were organized on Maps and the trees of association were built from the recollections of RMSFC/UESPI. This material brought to light the categories of analysis: the sense of practices, the sense of novelty and the sense of affection; and three subcategories: integrality as innovation in health care; movement caused by multiprofessional team work and learning with the community – the education-service-community integration. Integrality is seen as the main guideline to their new professional practices, indicating RMSFC/UESPI has enhanced professionals’ perception, bringing up all the meanings that the word carries. Factors like team work and integration with the community were constantly recalled by the professionals and were frequently followed by positive feelings, indicating that more emphasis must be given to these pedagogical tools, which are 10 considered “gold standard” for the formation of health care professionals, aiming at the commitment with care and resoluteness of the people’s demands for health. When the study found that the egressed professionals were scattered all over the Health Care Network, it observed the attempts to adapt theoretical and practical content learnt during Residency to the new work conditions. Like a milestone, RMSFC/UESPI stirred feelings and paved the way for the advent of new ways of care, backed by integrality in assistance, respect to individuals’ autonomy and by interpersonal relationships.